2022
DOI: 10.3389/fcell.2021.804105
|View full text |Cite
|
Sign up to set email alerts
|

Low pH Attenuates Apoptosis by Suppressing the Volume-Sensitive Outwardly Rectifying (VSOR) Chloride Current in Chondrocytes

Abstract: In a variety of physiological and pathophysiological conditions, cells are exposed to acidic environments. Severe synovial fluid acidification also occurs in a progressive state of osteoarthritis (OA) affecting articular chondrocytes. In prior studies extracellular acidification has been shown to protect cells from apoptosis but the underlying mechanisms remain elusive. In the present study, we demonstrate that the inhibition of Cl− currents plays a significant role in the antiapoptotic effect of acidification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Following the activation of caspase proteins, gasdermin family proteins have been revealed to cleave to separate their N-terminal pore-forming domain from the C-terminal repressor domain, and finally the N-terminal is inserted into cell membranes and forms large oligomeric pores, disrupting ion homeostasis and subsequently inducing osmotic swelling (27,36). Several studies, including the present one, have demonstrated that the blockage of chloride channels led to cell swelling in both isotonic and hypotonic conditions (8,23,29,40). It was also demonstrated that PTX could inhibit the background-, hypotonicity-and cisplatin-induced chloride currents in A2780 ovarian cancer cells (22).…”
Section: Discussionmentioning
confidence: 69%
“…Following the activation of caspase proteins, gasdermin family proteins have been revealed to cleave to separate their N-terminal pore-forming domain from the C-terminal repressor domain, and finally the N-terminal is inserted into cell membranes and forms large oligomeric pores, disrupting ion homeostasis and subsequently inducing osmotic swelling (27,36). Several studies, including the present one, have demonstrated that the blockage of chloride channels led to cell swelling in both isotonic and hypotonic conditions (8,23,29,40). It was also demonstrated that PTX could inhibit the background-, hypotonicity-and cisplatin-induced chloride currents in A2780 ovarian cancer cells (22).…”
Section: Discussionmentioning
confidence: 69%
“…While other chondrogenic cell lines, such as C28/I2, ATDC5, and C3H10T1/2, have been used for in vitro studies, they are not suitable for genome-wide growth-plate chondrocyte screening due to limitations of culture conditions and/or recapitulation of an articular cartilage phenotype. 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 Although use of the GPLC cell line enabled genome-wide screening, our chondrocyte maturation assay favors detection of KOs that have a proliferative advantage (most abundant KOs within the top/bottom 10% of mature/immature cells were selected). To account for this potential shortcoming, we considered background depletion of maturing cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 The extracellular matrix (ECM) of the articular cartilage mainly comprises type II collagen (Col II) and aggrecan (ACAN), and chondrocytes are wrapped in the lacuna, which is surrounded by a dense network of Col II and ACAN. 4,5 However, as the disease develops and progresses, many endogenous characteristic alterations become evident in the ECM, such as weakly acidic pH (5.0-6.5) of the synovial fluid 6 and overexpression of matrix metalloproteinases (MMPs; e.g., MMP3, MMP9, and MMP13). 7 However, these inherent traits of the damaged cartilage and microenvironment features in OA provide valuable references for its treatment.…”
Section: Introductionmentioning
confidence: 99%